Implementation of a peer review program using the validated DIET‐COMMS tool to assess dietitians' communication skills in the workplace. Issue 3 (4th September 2020) - Notaras, Stephanie; Smythe, Kylie; Mak, May; Whitehead, Kirsten
Abstract: Aims: Communication is the main method used by dietitians to conduct their practice. Yet, few evidence‐based tools are available to assess dietitians' communication skills to guide skill development. Further, workplace peer review programs for assessment of communication skills are not standard practice. DIET‐COMMS is a validated tool to assess dietitians' communication skills in patient consultations. The aims of this study were to implement a workplace peer review program using the DIET‐COMMS tool, assess dietitians' communication skills, evaluate inter‐rater reliability and dietitian satisfaction. Methods: Single site study within Australian hospital dietetics department. Training for DIET‐COMMS usage was undertaken with assessors (senior dietitians) and dietitians being assessed using an online training package and face‐to‐face group sessions. The peer review process consisted of two rounds, occurring four to six months apart. The first round was undertaken with two assessors to evaluate inter‐rater reliability. An online survey was conducted to evaluate dietitian satisfaction. Results: Seventeen dietitians completed the program. In the first round, 13 of 17 dietitians scored 76% to 100% on the DIET‐COMMS tool (median = 85%, interquartile range [IQR] = 77‐93). All dietitians scored 76‐100% (median = 98%, IQR = 94‐100) in the second round, with significantly higher scores compared to the first (98% vs 85%; P ‐value <.001). The intra‐class correlation coefficient was 0.86 (95% confidence interval = 0.64‐0.95), indicating good‐excellent inter‐rater reliability. All dietitians reported the tool measured the nutrition care process adequately and was applicable to practice. Conclusions: The peer review program using DIET‐COMMS was successfully implemented within a workplace environment. Widespread implementation of peer review programs using DIET‐COMMS is recommended as a standard practice for the profession.